Transshipment activities in the North Pacific Fisheries Commission Convention Area. (December 2022) - Saito, Rui; Oozeki, Yoshioki; Takasaki, Kenji; Saito, Tsutomu; Uehara, Shinji; Miyahara, Masanori
Abstract: At-sea transshipment, transfer of catch from a fishing vessel to a carrier vessel is largely practiced in distant water fisheries. In the Convention Area (CA) of the North Pacific Fisheries Commission (NPFC), major portions of catches are known to be transshipped from fishing vessels to carrier vessels. To achieve proper stock assessment and management of small pelagic species, Japanese sardine, mackerels, Pacific saury, and neon flying squid, the transshipment data during 2018 and 2019 were analyzed. Based on this data and the registered vessel list, the transshipment activities were clarified by the analysis of AIS data, and the amount of catch landed directly by fishing vessels to markets were estimated. The transshipments of Pacific saury were well-reported by the Members and generally corresponded with the catch data. The transshipments of Japanese sardine and mackerels were presumably under-reported due to several observed inconsistencies between the transshipment and catch data. Ongoing stock assessment concerning these two species is thought to produce a weak incentive to report the related transshipments accurately, resulting the under-reporting or reporting as "Others". Attempts were made to identify the transshipped species reported as "Others" by an analysis of AIS data and SST, and these were concluded as either transshipments of Japanese sardine or mackerels. The present study revealed transshipment activities of Members using the transshipment data and AIS data for the first time and indicated the Members report transshipment data accurately and that analysis of these activities can support the sustainable use of pelagic species within the CA.